Measuring the quality of a health research information system as basis for enhancement - Daulat, Grace Ruth T. (Animo Repository, 2022)
Purpose/objectives: This study aims to investigate the satisfaction of the users of HERDIN PLUS, a local health research database, based on the quality attributes of Delone & McLean’s information system success model (2003) as a basis for enhancing the system. Each quality attribute - system quality, information quality, and service quality- were tested to determine its effect on user satisfaction. Design, methodology, approach. This study used the mixed-method research design. A questionnaire consisting of closed and open-ended questions was used. Participants are identified through purposive sampling. The Google Form link was disseminated via email. A total of 110 responses were received. The quantitative data gathered were analyzed using the SPSS Statistics and qualitative responses were processed through thematic analysis. Multiple Regression analysis was applied to test the hypotheses. Findings. Information quality has the highest average satisfaction compared to the system and service quality category. In terms of per item analysis, having relevant information on HERDIN PLUS garnered the highest satisfaction from the respondents. Whereas, having dependable support service, system speed, and having the system to be always up and running were the items with the least satisfaction. System quality (t=3.967, p=.000) and service quality (t=6.829, p=.000) were found to affect user satisfaction significantly and positively. Support service dependability, system speed, and system reliability were considered priorities for improvement. Most of the comments from users were concerns related to system improvements. New features such as mobile application, messaging, and real-time notifications were also recommended. Alongside further system improvements, boosting information dissemination to users for already available features of the system was identified as necessary. Originality of the paper: This paper used Delone & McLean’s information system success model (2003) to determine user satisfaction with a local information system similar to a research database. This study contributes to providing a better understanding of user satisfaction by gathering quantitative and qualitative data.